2019
DOI: 10.1002/suco.201800215
|View full text |Cite
|
Sign up to set email alerts
|

Pretensioned pullout test of 18 mm (0.7 in.) diameter strand with different embedment lengths

Abstract: In this paper, a pretensioned pullout test method was proposed to better understand the bond mechanism and evaluate the bond behavior of pretensioned concrete members. A total of 15 pullout specimens with a centered 18‐mm (0.7 in.) diameter strand were tested. The specimens were divided into three sets according to their strand embedment lengths. For each set, there are two non‐pretensioned specimens and three pretensioned specimens with different initial prestress levels. In this way, the effects of the stran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…∆ ↓= 5ql 4 384E c I g (7) Accordingly, the predicted net cambers were 16.0 mm at 4 d detension and 15.2 mm at 6 d detension. In fact, the box girder was detensioned in the factory at the age of 6 days, and the measured camber was 15.3 mm.…”
Section: Cambermentioning
confidence: 90%
See 1 more Smart Citation
“…∆ ↓= 5ql 4 384E c I g (7) Accordingly, the predicted net cambers were 16.0 mm at 4 d detension and 15.2 mm at 6 d detension. In fact, the box girder was detensioned in the factory at the age of 6 days, and the measured camber was 15.3 mm.…”
Section: Cambermentioning
confidence: 90%
“…Morcous et al [1][2][3] demonstrated the specific problems of NU I-girders using 18-mm strands, and Ma et al [4] studied the transfer length and development length of AASHTO-PCI BT girders using two different high-capacity prestressing strands. Jiang et al [5][6][7] studied the bond properties of 18-mm strands through a pullout test of specimens with different embedment lengths and initial prestress forces. Dang et al [8][9][10], in the past ten years, have been studying the performances of pretensioned concrete beams using 18-mm strands.…”
Section: Introductionmentioning
confidence: 99%
“…Dang et al [9][10][11] systematically measured a large number of transfer lengths while studying the bonding performance of 18 mm strands. Jiang et al [12,13] conducted a study on the transfer length of 18 mm strands with pull-out tests, in which the failure mode, the relationship between the slip of strand and the pull-out force, and the relationship between the embedment length and the transfer length were analyzed.…”
Section: Introductionmentioning
confidence: 99%